BACKHAUL GAS TO UKRAINE: THE ESSENCE OF THE PROMLEM AND ITS IMPACT ON INTERNATIONAL RELATIONS IN THE ENERGY SECTOR - R. Murgas (Vestnik MGIMO-Universiteta)
The article examines the most important aspects of the problem of the reverse of gas to Ukraine, its significance and consequences for the further development of contemporary international relations in the energy sector between the Russian Federation (gas exporter), Ukraine (transit country) and the European Union (importer). Considering all the elements that are important for the analyzed problem, the answer to the question “how the reverse gas flow influenced the energy security of Russia, Ukraine and the European Union, and the relationship between them” is given, using the explicative method of content analysis and the analysis of several press conferences. To understand all the nuances of relationships in this triangle, a detailed description of the term “reverse gas flow” is offered, as well as an explanation of the differences between “physical” (or real) and “virtual” reverse, which play a key role in the study of this problem. The essence of the conflict lies in the fact that the parties have different points of view on the legitimacy of the so-called “virtual” backhaul. In contrast to the physical reverse, i.e. to the real gas flow through the pipeline, in case of a virtual or a paper reverse, a one-way gas flow takes place, part of the total volume of which the transit state buys and leaves on its territory. The EU and Ukraine believe that a virtual backhaul between them is possible according to the provisions of the Third Energy Package and its relevant norms, based on the fact that the EU countries and Ukraine are part of the so-called. Energy Community. Another point of view regarding virtual backhaul is Russian, which initially opposed virtual reverse on the grounds that the raw material is the property of the state-owned company OAO Gazprom until it crosses the western border of Ukraine. The article details the legal documents on which the above-mentioned countries rely, as well as the official statements of the parties. Based on the analysis conducted, it is concluded that reverse gas supplies to Ukraine represent a temporary and far from perfect scheme, which does not fundamentally solve the problem of disagreements between the EU, Ukraine and Russia in the energy sector, namely, the gas transit. Nevertheless, the observed increase in the volume of Russian natural gas supplies to the EU in 2016 and early 2017 and the forecast for a further demand increase for gas from Russia in the EU in the future indicates that the provision of gas transit through the territory of the Visegrad Group countries, Members of the EU from Southeastern Europe and the search for new ways of supply, as well as the preservation of some of the current ones, occupy the leading positions on the political agenda of the EU countries, Russia and Ukraine, as they relate to their energy security